POLITENESS CONSTRUCTION IN MANGGARAI CULTURE: A STUDY ON THE LINGUISTIC ASPECT OF MANGGARAI LANGUAGE - Semana, Ignasius Loy (STKIP Santu Paulus Ruteng, 2016)
Abstract: Politeness Construction In Manggarai Culture: A Study On The Linguistic Aspect Of Manggarai Language. Language is everything. Whatever people do in their daily life, when they come together, they use language. Language is tightly woven into human’s existence, that is, human is a thoughtful and ethical creation. In order to understand their humanity then we have to understand the language they use. Therefore, language is unique to human being because language it self can distinguish human from human, and human from animal. Human’s language is influenced by the social relationship between man and man. The construction of language chosen is indicated by the social status and the type of social relationship developed in the society. Conversely, the type of the social relationship and the social status are expressed in the construction of thechosenlanguage. The aim of the study, then, is to analyze and describe the construction of politeness developed in Manggarai society for the purpose of expressing the politeness in Manggarai culture. It is also to show the linguistic aspects developed in Manggarai language. Keywords: politeness, language construction, linguistic aspect, Manggarai language Abstrak: Bentuk-Bentuk Kesantunan Bahasa Dalam Budaya Manggarai: Sebuah Kajian Tentang Aspek-Aspek Linguistik Dalam Bahasa Manggarai. Bahasa adalah segala-galanya. Apapun yang dilakukan manusia dalam kehidupannya, apabila mereka berada bersama, mereka menggunakan bahasa. Bahasa melekat erat dalam eksistensi manusia sebagai makhluk berpikir dan bermoral. Untuk memahami jati diri seseorang maka kita harus memahami bahasa yang digunakan sebab bahasa membuat seseorang menjadi manusiawi. Bahasa manusia dipengaruhi oleh relasi sosial dengan sesama manusia. Bentuk bahasa yang dipakai sering kali ditentukan oleh jenis dan tingkatan relasi sosial dalam masyarakat. Sebaliknya, jenis dan tingkatan relasi sosial seseorang terlukis dalam bentuk bahasa yang digunakan. Tulisan ini membahas tentang bentuk bahasa yang digunakan oleh masyarakat Manggarai untuk menunjukkan keadaban masyarakat Manggarai dalam membangun relasi sosial. Tujuan penulisan ini adalah untuk memperkenalkan aspek-aspek linguistik dalam bahasa Manggarai dengan merujuk pada konstruksi bahasa yang digunakan dalam membangun relasi sosial yang santun dan beradab di antara masyarakat Manggarai. Kata kunci: kesantunan bahasa, bentuk bahasa, aspek linguistik, bahasa Manggarai